Prisoners of War: Black Female Incarceration at the End of the 1980s - Rolison, Garry L. (Social justice, 2002)
It is argued that race is central to any understanding of the increased rates of incarceration in the U.S. that began in the 1980s. A statistical analysis of black and white women who were incarcerated at the end of 1991 is presented. It is concluded that black women, more than any other demographic group, bore the brunt of the U.S. punitive policy against drugs that relied heavily on incarceration.